On normality of parabolic (φ, ξ η, λ)-structures - Baškienė, Angelė (Lietuvos matematikos rinkinys, 2003)
In the article necessary and sufficient conditions are found for the parabolic (φ, ξ  η,  λ)-structure to become normal.